PORTAL GSC: UMA FERRAMENTA PARA EXERCÍCIO DA CIDADANIA QUE UTILIZA O CMS JOOMLA - Allebrandt, Sérgio L.; Cavalheiro, Marcos R. M.; Stephanini, Jardel R.; Pereira, Ismael L. (Salão do Conhecimento, 2013)
Resumo